Super‐Stretchable Hybrid Aerogels by Self‐Templating Strategy for Cross‐Media Thermal Management. Issue 8 (3rd February 2023) - Shan, Xiameng; Hu, Peiying; Wang, Jing; Liu, Ling; Yuan, Dengsen; Zhang, Junxiong; Wang, Jin
Abstract: Personal thermal management (PTM) materials have attracted increasing attention owing to their application for personal comfort in an energy‐saving mode. However, they normally work in the same media such as in the air, and little is known about what will happen in other media like water. In this study, a system for cross‐media thermal management (CMTM): passive cooling in air and thermal insulation underwater is proposed. Hybrid aerogels comprising thermoplastic polyurethane (TPU) matrix and superhydrophobic silica aerogel particle (SSAP) for CMTM are designed and synthesized using a thermally induced phase separation and self‐templating strategy. The TPU matrix endows the aerogels with super stretchability (500%), shape memory, and outstanding healing recovery rate (89.9%), which are ideal characteristics for potential wearable usage. Additionally, the TPU and SSAP endow the aerogel with high solar reflectivity and infrared emissivity, thus achieving a sub‐ambient cooling of 10.6 °C in air. Moreover, the SSAP endows the aerogels with low thermal conductivity (0.052 W m −1 ·K −1 ) and high hydrophobicity (143°), enabling the aerogels for underwater thermal insulation. The CMTM performance of the aerogels makes them for potential uses in cross‐media environments such as reefs and islands where cooling in air and thermal insulation in water are required. Abstract : Silica – thermoplastic polyurethane hybrid aerogels with excellent stretchability and healability are designed and synthesized for cross‐media thermal management – passive daytime radiative cooling in air and thermal insulation in water, which is facilitated by high solar reflectance, high IR emissivity, high contact angle, and low thermal conductivity of the hybrid aerogel.